Advances in Metagenomics and Its Application in Environmental Microorganisms - Zhang, Lu; Chen, FengXin; Zeng, Zhan; Xu, Mengjiao; Sun, Fangfang; Yang, Liu; Bi, Xiaoyue; Lin, Yanjie; Gao, YuanJiao; Hao, HongXiao; Yi, Wei; Li, Minghui; et al. (Frontiers in Microbiology, 2021)
Metagenomics is a new approach to study microorganisms obtained from specific environment by functional gene screening or sequencing analysis. Metagenomics studies focus on microbial diversity, community constitute, genetic and evolutionary relationships, functional activities, interactions and relationships with the environment. Sequencing technologies have evolved from shotgun sequencing to high-throughput, next-generation sequencing (NGS), and third generation sequencing (TGS). NGS and TGS have shown the advantage of rapid detection of pathogenic microorganisms. With help of new algorithms, we can better perform the taxonomic profiling and gene prediction of microbial species. Functional metagenomics is helpful to screen new bioactive substances and new functional genes from microorganism and microbial metabolites. In this article, basic steps, classification and applications of metagenomics are reviewed.